A synopsis of Kiotina Klapálek, 1907 (Plecoptera: Perlidae) from China, with description of a new species from Zhejiang Province - Su, Tong; Chen, Zhi-Teng (Zootaxa, 2020)
A new species of Kiotina, K. yexiaohani sp. nov. is described from Zhejiang Province of southeastern China. The male of the new species is characterized by the V-shaped epiproct sclerite with thick, out-curved arms and a fusiform base. The apical half of subgenital plate sub-trapezoidal with a slightly notched apex distinguishes the female of the new species. Information on the types and available descriptions of Chinese Kiotina species are summarized. Additionally, an unassociated female of a Kiotina species is described and illustrated.